STUDYING THE EFFECT OF VITAMIN D AND CALCIUM PREPARATIONS IN THE TREATMENT OF OSTEOPOROSIS AFTER GLUCOCORTICOSTEROID THERAPY IN RHEUMATOID ARTHRITIS - Jumaniyazov Bexzod Kadirberganovich; Madaminov Xudayberdi Atabekovich; Matyaqubova Laylo Shixnazarovna (Scholar Express Journals, 2025)
This article discusses methods for preventing osteoporosis after glucocorticosteroid therapy in rheumatoid arthritis, the results of scientific studies, recommended methods, and directions.
Keywords: rheumatoid arthritis; osteoporosis; glucocorticosteroid therapy